Images of own Future of Mothers Having Children with Disabilities - Kovalenko, Alla; Traverse, Tetyana; Hryshchuk, Eliso (Social Welfare: Interdisciplinary Approach, 2018)
The article presents the results of research on images of own future for mothers having children without health problems and with disabilities. The differences in the psychological characteristics and time perception of the mothers having children without health problems and with disabilities were found: the mothers having children with disabilities are more negatively perceive the past and estimate higher the present (both hedonistic and fatalistic); mothers having children without health problems percept the past more positively. It’s also shown that there is the statistically significant difference between the groups concerning time perception. The article determines that the peculiarities of time perception are determined by the psychological characteristics of mothers, such as their awareness of life and its components, self-actualization and its components, which is reflected in multiple correlations.
Keywords: image of the future; time perspective; time perception; children with disabilities